Foreign correspondent [videorecording (DVD)] - McCrea, Joel, 1905-1990; Day, Laraine, 1920-2007; Marshall, Herbert, 1890-1966 (Criterion collection, 2014)
A full-throttle espionage thriller, starring Joel McCrea as a green Yank reporter sent to Europe to get the scoop on the imminent war. It's wall-to-wall witty repartee, head-spinning plot twists, and brilliantly mounted suspense set pieces, including an ocean plane crash climax with astonishing special effects.